Nonwoven Textiles from Hyaluronan for Wound Healing Applications - Kubíčková, Jolana; Medek, Tomáš; Husby, Jarmila; Matonohová, Jana; Vágnerová, Hana; Marholdová, Lucie; Velebný, Vladimír; Chmelař, Josef (Biomolecules, 2021)
Nonwoven textiles are used extensively in the field of medicine, including wound healing, but these textiles are mostly from conventional nondegradable materials, e.g., cotton or synthetic polymers such as polypropylene. Therefore, we aimed to develop nonwoven textiles from hyaluronan (HA), a biocompatible, biodegradable and nontoxic polysaccharide naturally present in the human body. For this purpose, we used a process based on wet spinning HA into a nonstationary coagulation bath combined with the wet-laid textile technology. The obtained HA nonwoven textiles are soft, flexible and paper like. Their mechanical properties, handling and hydration depend on the microscale fibre structure, which is tuneable by selected process parameters. Cell viability testing on two relevant cell lines (3T3, HaCaT) demonstrated that the textiles are not cytotoxic, while the monocyte activation test ruled out pyrogenicity. Biocompatibility, biodegradability and their high capacity for moisture absorption make HA nonwoven textiles a promising material for applications in the field of wound healing, both for topical and internal use. The beneficial effect of HA in the process of wound healing is well known and the form of a nonwoven textile should enable convenient handling and application to various types of wounds.
Keywords: hojení ran; mechanical properties; obvazy; buňky 3T3; Humans; Bandages; wet spinning; testování materiálů; lidé; textilie; zvířata; myši; Wound Healing; Mice; nonwoven textile; 3T3 Cells; wound dressing; hyaluronan; Textiles; kyselina hyaluronová; Animals; Hyaluronic Acid; Materials Testing